STATUS OF DIGESTIVE SYSTEM OF THE CHILDREN, SUFFERING FROM CARDIOREUMATOLOGIC PATHOLOGY - E.P. Sitnikova ("Paediatrician" Publishers LLC, 2007)
The article provides the findings of observation for the children, suffering from cardioreumatologic pathology. The author reveals the high spread of the gastrointestinal tract diseases among the children from this category. She makes a number of conclusions on the syntropy and interference of digestive and cardiovascular system diseases. This relation indicates the necessity to carry out a complex examination of the children and provide interaction between the cardiologists and gastroenterologists.Key words: children, heart and joint diseases, diseases of the digestive organs.